Lutas por reconhecimento, racismo e silenciamento : um estudo de caso de conversações em ambientes digitais - Deize Ferreira Paiva Lopes (2021)
If, on the one hand, mobilizations and black activism works through the digital platforms, on the other, these spaces perpetuate, if not deepen, racial bias. In order to approach the black racial struggle and the invisibility strategies in digital platforms, this work discusses recognition and silencing. The aim is to understand, from the online conversations triggered by the video “Peppa NÃO!”, originally published on Youtube, how the communicative modes of this interactional dynamic affect the struggle for recognition and the respect of the black body. An analysis was made of the repercussions of the suspension of the children's book Peppa (2009), which provoked a discussion about racist stereotypes. The bibliography is based on Axel Honneth's Theory of Recognition and the production of knowledge by authors whom discuss the perspective of the black racial issue, such as Patricia Hill Collins, Lélia Gonzalez, Nilma Lino Gomes and Silvio Almeida. By discussing the Theory of Recognition in Honneth, these authors provide subsidies to indicate the existence of gaps in the theory: a) the dehumanizatio of the black person as a subject of recognition, b) the historical silencing to which this group is subjected and c) the difficulties of repair of injustices. The methodology adopted consists of quantitative and qualitative content analysis of the 2,273 comments triggered by the suspension of the book, which were found in six videos on Youtube, one publication on Facebook, and on six news sites and blogs was made. The results found point to the following scenario: I) the term racism is under negotiation, in general, people understand that this oppression exists, but there are disputes as to its definition; II) the dehumanization, silencing and non-repair of injustices make it difficult for black people to fight for recognition; III) different communicative modes help to uncover oppressions, at the same time they may contain silencing strategies by individualizing issues and invalidating experiences of injustice; in particular, IV) attacks can also function as a way of denouncing the damage suffered and the forms of injustice and oppression.